Bidirectional Association Between Physical Activity and Dopamine Across Adulthood—A Systematic Review - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Physical activity (PA) may influence the secretion of neurotransmitters and thereby have positive consequences for an individual’s vulnerability (i.e., reducing anxiety and depressive symp-toms). This systematic review aims to analyse the potential bidirectional effects of exercise on dopamine from young adulthood to old age. The article search was conducted in PubMed, Scopus, and Web of Science in December 2020. The inclusion criteria were longitudinal and experimental study design; outcomes included dopamine and exercise; effect of exercise on dopamine and vice versa; adults; and articles published in English, Portuguese, or Spanish. Fifteen articles were included in the review. We observed robust findings concerning the potential effects of PA on dopamine, which notably seem to be observable across a wide range of participants characteristics (including age and sex), a variety of PA characteristics, and a broad set of methods to analyse dopamine. By contrast, regarding the potential effects of dopamine on PA, findings were mixed across studies. Thus, there are robust effects of physical exercise on dopamine. These findings further strengthen the idea that innovative approaches could include PA interventions for treating and preventing mental disorders. Therefore, it seems that PA is a potential alternative to deal with mental health issues. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.